Bridging Homelessness and Mental Health Crisis Care in Indonesia: A Nursing Response to Gilmore Et al. - Raup Padillah (Journal of Psychiatric and Mental Health Nursing, 2026)
ABSTRACT This paper is highly relevant to mental health nursing because it highlights the critical role of psychiatric and mental health nurses in addressing the intersection between homelessness, social exclusion, mental health crisis and substance‐use problems. It emphasises that nurses are not only involved in crisis assessment and clinical care, but also in outreach, trauma‐informed communication, continuity of medication, discharge planning, family engagement and coordination with community and social services. By proposing integrated, low‐threshold and community‐based crisis pathways in Indonesia, the paper strengthens the contribution of mental health nursing to equity, dignity, prevention and rights‐based care for vulnerable populations.